2017
DOI: 10.1038/srep40858
|View full text |Cite
|
Sign up to set email alerts
|

Local melatonin application induces cold tolerance in distant organs of Citrullus lanatus L. via long distance transport

Abstract: Melatonin is a ubiquitous chemical substance that regulates plant growth and responses to stress. Several recent studies show that exogenous melatonin confers cold tolerance to plants; however, the underlying mechanisms remain largely unknown. Here, we report that melatonin application at optimal dose, either on the leaves or the roots, not only induced cold stress tolerance in the site of application, but also systemically induced cold tolerance in untreated distant parts. Foliar or rhizospheric treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 60 publications
(78 reference statements)
1
80
0
1
Order By: Relevance
“…53,54 Conversely, melatonin regulates root development independent of the auxin signaling response, 55 suggesting a complex relationship between melatonin and auxins. Melatonin also interacts with other hormones such as GA, cytokinins, ethylene, and abscisic acid; 16,17,56,57 however, no study has reported the possible involvement of BR in response to melatonin in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Conversely, melatonin regulates root development independent of the auxin signaling response, 55 suggesting a complex relationship between melatonin and auxins. Melatonin also interacts with other hormones such as GA, cytokinins, ethylene, and abscisic acid; 16,17,56,57 however, no study has reported the possible involvement of BR in response to melatonin in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The original function of melatonin is believed to have been as a free radical scavenger in cyanobacteria, and thereafter, it has additionally functioned to enhance plant seedling growth and seed germination during evolution, as in animals. 3 Many roles played by melatonin in plants are associated with antioxidant activity, 4,5 which is involved in many defense responses against a diverse array of abiotic stressors, such as high pH, 6 heavy metals, [7][8][9][10][11] drought, 12,13 salt, 14,15 cold, 16 high temperature, 17,18 and high nitrate concentration 19 by modulating many corresponding regulatory pathways. 20 In addition, melatonin also plays a role in protecting plants from attack by various pathogens, possibly by way of mitogen-activated protein kinases.…”
Section: Introductionmentioning
confidence: 99%
“…19,28 SNAT (which catalyzes the penultimate biosynthetic step) is expressed in both chloroplasts 29 and mitochondria 30 whereas the enzyme catalyzing the ultimate step (N-acetylserotonin methyltransferase [ASMT]) is expressed in both the cytoplasm 29 and chloroplasts. 20 Melatonin protects plants against both biotic and abiotic stresses, [31][32][33][34][35][36][37] and plays roles in plant growth and development. 14,[38][39][40][41][42][43][44] In recent decades, the physiological and biochemical roles of plant melatonin have been studied both pharmacologically and via molecular genetics, but no inhibitors of SNAT or ASMT have been described.…”
Section: Introductionmentioning
confidence: 99%
“…These 29 genes also exhibited variable lineage-specific positive selection within Portulacineae (table 2). The strongest signals of positive selection were all found in genes associated with drought and/or cold tolerance in the ABA signaling pathway (such as the NAC10/29 and WRKY33 TFs, the CDPK18 and the PP2Cs, e.g., Golldack et al 2014; Nakashima et al 2014; Huang et al 2015; Li et al 2017), a central regulator of abiotic stress resistance. Interestingly, the ABI1 and PP2CA genes, which encode two proteins of the PP2Cs family, were among the genes with the highest number of lineages under positive selection.…”
Section: Resultsmentioning
confidence: 99%